Rheumatoid Arthritis-Associated MicroRNA-155 Targets SOCS1 and Upregulates TNF-α and IL-1β in PBMCs - Li, Xiaochuan (Molecular Diversity Preservation International (MDPI), 2013)
miR-155 plays a crucial role in proinflammatory activation. This study was carried out to assess the association of abnormal expression of miR-155 in peripheral blood of patients with Rheumatoid arthritis with the expression of TNF-α and IL-1β. Release of TNF-α and IL-1β, and expression of miR-155 were determined in RA peripheral blood or peripheral blood macrophages, followed by correlation analysis of the cytokines release and miR-155 expression. Furthermore, in vitro studies indicate that miR-155 inhibited the expression of SOCS1. Our results suggest that there is a correlation between the high-level expression of miR-155 and the enhanced expression of TNF-α and IL-1β. miR-155 targets and suppresses the expression of SOCS1, and the decrease of SOCS1 may lead to the upregulation of TNF-α and IL-1β.